Control y sincronización de la zona horaria UTC-5 en la red de comunicación del Centro de Metrología de las FF.AA. - Zapata Calderón, Jonathan Xavier (2018)
The Center for Metrology of the Ecuadorian Army (CMEE), is located in the facilities of the Rumiñahui Military Fort, the proposal was proposed to solve the failures of synchronization, calibration, reference of patterns, which exist in laboratories, for this reason, the development and analysis was established, for the control and synchronization of the Time Zone UTC-5 through an NTP server (Network Time Protocol), based on a rubidium oscillator; these help to provide the services of synchronization, georeferencing, calibration and / or characterization of measuring equipment and reference standards in the electrical quantities, time, frequency; The results created by the aforementioned equipment are compared in the Common View system, where the information of the time lags and deviations generated by the Laboratories belonging to the SIM (Inter-American Metrology System) is displayed. The present study was also carried out with the purpose of establishing the control and administration of the NTP service, as an application for the Metrology Center and as a time and frequency reference through the signals 1, 5, 10 MHz, 1PPS, which they are required as parameters of initialization by the BIPM, which is an organization that governs the standards for the execution of the system, determining that the CMEE, provide said services, with a time deviation of 1ms in relation to the NIST Laboratory (National Institute of Standards and Technology), where the comparison time does not exceed 50ns, this guarantees that the services generated by the institution have a high precision, accuracy and efficiency, for any user that requires it.